Suppression of bone remodeling associated with long-term bisphosphonate treatment is mediated by microRNA-30a-5p. Issue 4 (1st April 2022) - Li, Xia; Xu, Ruisheng; Ye, Jun-Xing; Yuan, Feng-Lai
ABSTRACT: Oral bisphosphonates (BPs) are a first-line treatment for osteoporosis. It is becoming a hot topic to identify new indicators for the early prediction of therapeutic effects and adverse reactions during the long-term use of BPs. To determine whether microRNA (miRNA) expression is modulated by long-term BPs treatment, we performed miRNA expression profiling analysis in patients receiving long-term BP treatment for postmenopausal OP. To assess the effect of BPs on miRNA expression, we used an Affymetrix Genechip miRNA array to analyze serum samples obtained from postmenopausal OP patients on long-term BP treatment and healthy controls. MiRNAs affected by BPs and their predicted targets were examined. We also investigated the effects of miRNA on osteoblast differentiation in vitro and on ovariectomy-induced bone loss in vivo. We observed that the level of miR-30a-5p was significantly increased in patients receiving long-term BP treatment for postmenopausal OP. Furthermore, miR-30a-5p was negatively correlated with bone formation. Consistent with this, in vitro osteoblast activity and matrix mineralization were increased by an antagomir of miR-30a-5p and decreased by an agomir of miR-30a-5p. We also found that miR-30a-5p directly targeted RUNX1 to inhibit osteoblastic differentiation. Consistent with the in vitro results, miR-30a-5p antagomir administration promoted bone formation in ovariectomized mice. Our findings identified miR-30a-5p as a novel mediator of long-term BP treatment that regulates bone formation in postmenopausal OP patients. GA: uf0001